Complementary and Alternative Medicine for Dysmenorrhea Caused by Endometriosis: A Review of Utilization and Mechanism. (3rd July 2021) - Guo, Ying; Liu, Fang-Yuan; Shen, Ying; Xu, Jia-Yue; Xie, Liang-Zhen; Li, Shi-Ying; Ding, Dan-Ni; Zhang, Dan-Qi; Han, Feng-Juan
Abstract : Endometriosis (EM) is a common and benign estrogen-dependent gynecological disorder among women of reproductive age, and secondary dysmenorrhea is one of the more severe symptoms. However, the mechanism behind the development of dysmenorrhea is poorly understood, and there is a lack of effective methods for diagnosing and treating EM dysmenorrhea. In this regard, complementary and alternative medicine (CAM) has recently come into widespread use due to its limited adverse reactions and high efficiency. This review updates the progress of CAM in the treatment of EM dysmenorrhea and seeks to identify the therapeutic efficacy as well as the mechanisms behind these effects based on the available clinical and experimental studies. According to the literature, CAM therapy for EM dysmenorrhea, including herbs (herbal prescriptions, extracts, and patents), acupuncture, and Chinese herbal medicine enema (CHM enema), is effective for relieving dysmenorrhea with fewer unpleasant side effects when compared to hormonal and surgical treatments. In addition, we discuss and analyze the existing gaps in the literature. We hope to provide some instructive suggestions for clinical treatment and experimental research in the future.